The teaching of social sciences in primary school Analysis of teaching Approaches within the Digital Classroom (Praxis Educativa, 2019)
The general problem that guides the work is related to the use of Information Technology and Educational Communication (TICE) that teachers do in Social Sciences classes in primary schools. The methodology used was to make a cut of the reality, to focus on three different moments of a didactic situation. First of all, an interview with the teacher focused on the planning of the didactic sequence to be implemented, a second moment of observation and recording of the didactic activity through the videocopy technique, and for the last time a self-confrontation interview. The analysis aims to show, in a general way, how teachers in social science classes make use of the Digital Mobile Classrooms (ADM).
Keywords: social sciences; primary; TICE (Educational Information and Communication Technologies).